1986
DOI: 10.1007/bf00315454
|View full text |Cite
|
Sign up to set email alerts
|

Projection from the inferior colliculus to the superior olivary complex in the albino rat

Abstract: The origin and termination of the fibers projecting from the inferior colliculus to the superior olivary complex have been studied in rat by means of the Fink and Heimer and horseradish peroxidase techniques (anterograde and retrograde transport of free horseradish peroxidase and peroxidase conjugated to wheat germ agglutinin). The colliculoolivary fibers originate in layer 3 of the external cortex and the adjacent part of the central nucleus, particularly in the former. Via the lateral lemniscus the fibers re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
71
0
2

Year Published

1996
1996
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(82 citation statements)
references
References 49 publications
9
71
0
2
Order By: Relevance
“…mRNA for CCK is found abundantly in neurones of the central nucleus of the inferior colliculus (Schiffmann and Vanderhaeghen, 1991;Wynne et al, 1995) and this higher centre is known to be a source of descending projections to the SOC (Caicedo and Herbert, 1993;Faye-Lund, 1986;Schofield and Cant, 1999;Thompson and Thompson, 1993;Vetter et al, 1993). As has already been mentioned, injection of anterograde tracer into the central nucleus of inferior colliculus gives rise to terminals within the ventral-most parts of the VNTB whose distribution within this nucleus is similar to that of CCKlabeled fibres.…”
Section: Origin Of Peptidergic Innervationmentioning
confidence: 75%
“…mRNA for CCK is found abundantly in neurones of the central nucleus of the inferior colliculus (Schiffmann and Vanderhaeghen, 1991;Wynne et al, 1995) and this higher centre is known to be a source of descending projections to the SOC (Caicedo and Herbert, 1993;Faye-Lund, 1986;Schofield and Cant, 1999;Thompson and Thompson, 1993;Vetter et al, 1993). As has already been mentioned, injection of anterograde tracer into the central nucleus of inferior colliculus gives rise to terminals within the ventral-most parts of the VNTB whose distribution within this nucleus is similar to that of CCKlabeled fibres.…”
Section: Origin Of Peptidergic Innervationmentioning
confidence: 75%
“…Previous work has shown that OC neurons receive inputs from two subdivisions of the cochlear nucleus (Warr, 1969;Robertson and Winter, 1988;Thompson and Thompson, 1991a;Ye et al, 2000), from the inferior colliculus (Faye-Lund, 1986;Thompson Fig. 8.…”
Section: Possible Origins Of Inputsmentioning
confidence: 98%
“…One descending source of input is from the inferior colliculus (Faye-Lund, 1986;Thompson and Thompson, 1993;Vetter et al, 1993). The MOC neurons can be activated by stimulating the inferior colliculus and the activation produces cochlear effects (Mulders and Robertson, 2000c;Ota et al, 2004).…”
Section: Possible Origins Of Inputsmentioning
confidence: 99%
“…Recent anatomical Vetter et al, 1993) and physiological (Rajan, 1990) data indicate that descending collicular fibers contact medial olivocochlear neurons, suggesting a direct relationship between the second and the third steps of the descending auditory pathway. The situation, however, is less clear within the IC: Whereas most descending neocortical fibers seem to innervate the dorsal and lateral regions of the IC, but not its central nucleus (CNIC; reviewed by Faye-Lund, 1985;Herbert et al, 1991), most colliculoolivary neurons are located more ventrally, mainly in the CNIC and the external cortex of the IC (ECIC; Faye-Lund, 1986). According to these data, there would be a partial, but presumably significant, segregation between the place of termination of the corticocollicular fibers and the location of the colliculoolivary neurons; those colliculoolivary neurons located in the CNIC do not appear to be under direct neocortical influence.…”
Section: E Saldana Et Almentioning
confidence: 99%